2013
DOI: 10.1002/cctc.201200712
|View full text |Cite
|
Sign up to set email alerts
|

From Oxide‐Supported Palladium to Intermetallic Palladium Phases: Consequences for Methanol Steam Reforming

Abstract: This Minireview summarizes the fundamental results of a comparative inverse-model versus real-model catalyst approach toward methanol steam reforming (MSR) on the highly CO2-selective H2-reduced states of supported Pd/ZnO, Pd/Ga2O3, and Pd/In2O3 catalysts. Our model approach was extended to the related Pd/GeO2 and Pd/SnO2 systems, which showed previously unknown MSR performance. This approach allowed us to determine salient CO2-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 89 publications
(160 reference statements)
2
72
0
Order By: Relevance
“…A plausible explanation is to posit that under the reaction mixture, and upon heating to 623 K, the surface of the metal crystallites became modified, richer in full 3D active PdZn ensembles, most likely owing to an increase of the Pd-Zn alloying which -in turndecreased methanol decomposition. This is entirely consistent with recent literature reports [4,28] and our XPS data, as shown below.…”
Section: Catalysts Performancesupporting
confidence: 94%
See 3 more Smart Citations
“…A plausible explanation is to posit that under the reaction mixture, and upon heating to 623 K, the surface of the metal crystallites became modified, richer in full 3D active PdZn ensembles, most likely owing to an increase of the Pd-Zn alloying which -in turndecreased methanol decomposition. This is entirely consistent with recent literature reports [4,28] and our XPS data, as shown below.…”
Section: Catalysts Performancesupporting
confidence: 94%
“…In particular, the presence of well-dispersed ZnO domains on the support surface and/or as patches onto the PdZn bimetallic crystallites under MSR reaction condition, seems to be crucial for obtaining high turnover frequencies. Nonetheless, other authors have concluded that just the right PdZn alloy (namely, tetragonal PdZn␤ 1 ) suffices to grant high S CO2 and high TOF values [26], albeit under MSR conditions oxidized Zn species seem to be present in their pre-reduced bimetallic particles as was suggested by Lorenz et al [28] based on their relevant XPS spectra, probably because those alloy powders were again exposed to water.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, there was an indication that addition of Zn to Pt or Pd altered the barriers for C-H cleavage and thus changed the stability of various intermediates in MSR [22]. The PdZn/ZnO interface was found to increase water activation at lower temperatures, therefore promoting CO2 selectivity [23]. However, the role of ZnO in the performance of PdZn/ZnO is not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%